2011
DOI: 10.1016/j.cpc.2010.12.053
|View full text |Cite
|
Sign up to set email alerts
|

PLATYPUS: A code for reaction dynamics of weakly-bound nuclei at near-barrier energies within a classical dynamical model

Abstract: A self-contained Fortran-90 program based on a three-dimensional classical dynamical reaction model with stochastic breakup is presented, which is a useful tool for quantifying complete and incomplete fusion, and breakup in reactions induced by weakly-bound two-body projectiles near the Coulomb barrier. The code calculates (i) integrated complete and incomplete fusion cross sections and their angular momentum distribution, (ii) the excitation energy distribution of the primary incomplete-fusion products, (iii)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 17 publications
2
99
0
Order By: Relevance
“…The massive transfer of 5,6 He for 7 Li was also observed and the breakups of 6 He+p and 5 He+d were not observed due to the high breakup threshold. The result of a classical dynamic model [10][11][12] gave a good agreement with the experimental data and explained the critical role of different cluster structures of 7 Li in the dynamics of reaction mechanism for the first time. These calculations clearly illustrated a two step process, breakup followed by fusion, in case of the capture of t and α clusters.…”
Section: Introductionsupporting
confidence: 65%
“…The massive transfer of 5,6 He for 7 Li was also observed and the breakups of 6 He+p and 5 He+d were not observed due to the high breakup threshold. The result of a classical dynamic model [10][11][12] gave a good agreement with the experimental data and explained the critical role of different cluster structures of 7 Li in the dynamics of reaction mechanism for the first time. These calculations clearly illustrated a two step process, breakup followed by fusion, in case of the capture of t and α clusters.…”
Section: Introductionsupporting
confidence: 65%
“…In Ref. [34], a three-dimensional classical dynamical reaction model [37][38][39] together with the measured prompt-breakup probabilities was adopted to study the systematics of the suppression for the reactions induced by 9 Be. It was found that the CF suppression is nearly independent of the target.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been developed in close collaboration with experimenters [3,4]. The model is implemented in the PLATYPUS code [5].…”
Section: The Platypus Modelmentioning
confidence: 99%